Genetic associations and parent-of-origin effects of PVRL1 in non-syndromic cleft lip with or without cleft palate across multiple ethnic populations - Ji Wan Park; Geon Kang; Seung-Hak Baek; Young Ho Kim (Epidemiology and Health)
OBJECTIVES This study investigated the associations of PVRL1 gene variants with non-syndromic cleft lip with or without cleft palate (NSCL/P) by evaluating transmission distortion and parent-of-origin (POO) effects in multiple ethnic populations. METHODS We conducted allelic and genotypic transmission disequilibrium tests (TDT) on 10 single-nucleotide variants (SNVs) in PVRL1 using data from 142 Korean families with an affected child. POO effects were analyzed using the POO likelihood ratio test, comparing transmission rates of maternally and paternally inherited alleles. To assess generalizability and ethnic heterogeneity, we compared results from Korean families with data from the Center for Craniofacial and Dental Genetics, which included 2,226 individuals from 497 European and 245 Asian trios. RESULTS TDT analysis identified significant over-transmission of the rs7940667 (G361V) C allele in Korean families (p=0.007), a finding replicated in both Asian (p=6.5×10-7) and European families (p=1.6×10-10). Eight SNVs showed strong TDT evidence in larger Asian and European datasets after multiple comparison corrections (p<0.0073). Of these, 4 SNVs (rs7940667, rs7103685, rs7129848, and rs4409845) showed particularly robust association (p<5×10-8). POO analysis revealed significant maternal over-transmission of the rs10790330-A allele in Korean families (p=0.044). This finding was replicated in European families (p=9.0×10-4). Additionally, 3 other SNVs, rs7129848 (p=0.001) and the linked SNVs rs3935406 and rs10892434 (p=0.025), exhibited maternal over-transmission in the validation datasets. CONCLUSIONS Our findings provide robust evidence supporting the associations of PVRL1 variants with NSCL/P susceptibility. Further research is necessary to explore the potential clinical applications of these findings.